A Comparative Study: The Precision of CNC Machines Using a Sliding Mode Controller (SMC) and a Wi-Fi ESP32 - Rifki Hermana; Muhammad Fahrur Aza; Yuris Setyoadi (Jurnal Teknik Mesin Mechanical Xplore, 2023)
Computerized numerical control (CNC) is one example of advances in automated machine technology. CNC can fulfil high precision and complex product specifications. Industrial CNC milling is still expensive regarding the hardware and software required to operate it. As a result, CNC milling machines are only used by large companies, with only a few mid-sized industries using them. It makes it impossible for medium enterprises to compete with large industries in terms of quality and output. This research aims to develop a CNC that uses an offline Wi-Fi controller based on ESP32 as an application that supports CNC machine work processes for use in small and medium enterprises. In an experiment, the precision of a CNC milling machine equipped with a sliding mode controller (SMC) controller was compared with that of a CNC machine equipped with an ESP-32 Wi-Fi controller. The CNC milling process with SMC control exceeds the tolerance limits in three dimensions based on the results of ten tests, namely length, width, and height or depth. Six values, two in each dimension of length, width, and height or depth, exceeded tolerance limits due to the CNC milling machine's ESP32 Wi-Fi control. Therefore, the CNC with SMC control is more accurate than the ESP32 Wi-Fi control because there are fewer failures with the former. This research has been carried out and provides input for the implementation of SMC, which can be considered in the CNC milling process.